Innovative food processing technologies : advances in multiphysics simulation - Knoerzer, Kai (Chichester, West Sussex, UK : Wiley-Blackwell/IFT Press, 2011)
"Multiphysics simulation of emerging food processing technologies discusses how multiphysics modeling - i.e., the simulation of the entire process comprising the actual equipment, varying process conditions and the physical properties of the food to be treated - can be applied in the development, optimization and scale-up of emerging food processing technologies and shows the most recent research outcomes to demonstrate process efficiency and the impact on scalability, safety and quality. Technologies covered include: high pressure processing, high pressure thermal sterilization, radiofrequency, microwave, ultrasound, ultraviolet, and pulsed electric fields processing. The book is targeted to food and process engineers, food technologists, equipment designers, and research and development personnel including microbiologists, both in industry and academia. Multiphysics simulation of emerging food processing technologies fully describes the importance and the methods for applying multiphysics modeling for the design, development, and application of these technologies"
1. Introduction to innovative food processing technologies : background, advantages, issues and need for multiphysics -- 2. The need for thermophysical properties in simulating emerging food processing -- 3. Neural networks : their role in high pressure processing -- 4. Computational fluid dynamics applied in high pressure processing scale up -- 5. Computational fluid dynamics applied in high pressure high- temperature processes : spore inactivation distribution and process optimization -- 6. Computer simulation for microwave heating -- 7. Simulating and measuring transient three-dimensional temperature distributions in microwave processing -- 8. Multiphysics modeling of ohmic heating -- 9. Basics for modeling of pulsed electric field processing of foods -- 10. Computational fluid dynamics applied in pulsed electric field preservation of liquid foods -- 11. Novel, multi-objective optimization of pulsed electric field processing for liquid food treatment -- 12. Modeling the acoustic field and streaming induced by an ultrasonic horn reactor -- 13. Computational study of ultrasound-assisted drying of food materials -- 14. Characterization and simulation of ultraviolet processing of liquid foods using computational fluid dynamics -- 15. Multiphysics modeling of ultraviolet disinfection of liquid food - performance evaluation using a concept of disinfection efficiency -- 16. Continuous chromatographic separation technology -- modeling and simulation -- 17. The future of multiphysics modeling of innovative food processing technologies
Includes bibliographical references and index
Keywords: Food industry and trade -- Mathematical methods; Food industry and trade -- Simulation methods